RP-HPLC METHOD FOR ESTIMATION OF AN ANTIPSYCHOTIC DRUG - PIMOZIDE - Kabra, Prachi; Nargund, L.V.G.; Srinivasa Murthy, M. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective – To develop and validate RP-HPLC method for estimation of Pimozide in bulk and its tablet dosage form. Method- Chromatographic separation was carried out on Grace Smart RP-18 column (250 mm X 4.6 mm inner diameter; 5µm particle size) using a mobile phase consisted of Acetonitrile: 50 mM Disodium hydrogen phosphate buffer (pH 6.2, adjusted by 1 % ortho phosphoric acid) in the ratio of 60: 40 %v/v. The flow rate was maintained at 1 ml/min and UV detection was measured at 280 nm. Propyphenazone was used as an internal standard. Results-The calibration curve of Pimozide was linear in range of 5- 100 µg/ml. The mean % assay of marketed formulation was found to be 101.02 % and % recovery was observed in the range of 99.23- 101.91 %. Relative standard deviation for precision study was found less than 2 %. The LOD and LOQ values were found to be 0.553 µg/ml and 1.678 µg/ml respectively. Conclusion- The developed method is simple rapid and easy to apply, making it suitable for routine analysis of Pimozide in bulk and tablet dosage form. KEYWORDS- Pimozide, RP-HPLC, Validation